Advantages and disadvantages of microarrays to study microbial population dynamics a minireview - Everett, K.R.; Rees-George, J.; Pushparajah, I.P.S.; Janssen, B.J.; Luo, Z. (New Zealand Plant Protection, 2010)
Microbial ecology is challenging because of practical problems associated with detecting and quantifying populations Bacteria and yeasts are not easily identified using conventional methods such as dilution plating and biochemical tests Those methods lack sensitivity are extremely timeconsuming and cannot account for unculturable organisms New DNAbased technology such as microarrays offers solutions to those problems However identification of microorganisms using DNA methodology is becoming increasingly complicated due to the variation revealed in sequenced microbe genomes Identification is no longer considered reliable when only one area of the genome is targeted and recent publications consider that sequences from six or seven different genes are required to resolve species or pathovars of fungi and bacteria reliably A large number of probes from different genes can be included on a single microarray chip The advantages and disadvantages of microarrays versus other DNA methods for studying microbial ecology of fruit surfaces are discussed